Quantified energy dissipation rates in the terrestrial bow shock: 2. Waves and dissipation. Issue 8 (25th August 2014) - Wilson, L. B.; Sibeck, D. G.; Breneman, A. W.; Contel, O. Le; Cully, C.; Turner, D. L.; Angelopoulos, V.; Malaspina, D. M.
Abstract We present the first quantified measure of the energy dissipation rates, due to wave‐particle interactions, in the transition region of the Earth's collisionless bow shock using data from the Time History of Events and Macroscale Interactions during Substorms spacecraft. Our results show that wave‐particle interactions can regulate the global structure and dominate the energy dissipation of collisionless shocks. In every bow shock crossing examined, we observed both low‐frequency (<10 Hz) and high‐frequency (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1c9p6v1w" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />≳</alternatives>10 Hz) electromagnetic waves throughout the entire transition region and into the magnetosheath. The low‐frequency waves were consistent with magnetosonic‐whistler waves. The high‐frequency waves were combinations of ion‐acoustic waves, electron cyclotron drift instability driven waves, electrostatic solitary waves, and whistler mode waves. The high‐frequency waves had the following: (1) peak amplitudes exceeding δB∼ 10 nT and δE∼ 300 mV/m, though more typical values were δB∼ 0.1–1.0 nT and δE∼ 10–50 mV/m; (2) Poynting fluxes in excess of 2000 μW m−2 (typical values were ∼1–10 μW m−2); (3) resistivities > 9000 Ω m; and (4) associated energy dissipation rates >10 μW m−3. The dissipation rates due to wave‐particle interactions exceeded rates necessary to explain the increase in entropy across the shock ramps for ∼90% of the wave burst durations. For ∼22% of these times, the wave‐particle interactions needed to only be ≤ 0.1% efficient to balance the nonlinear wave steepening that produced the shock waves. These results show that wave‐particle interactions have the capacity to regulate the global structure and dominate the energy dissipation of collisionless shocks.